The Effect Of Good Corporate Governance, Intellectual Capital, And Leverage On Firm Value With Profitability As Mediation Variable (Study On Registered Non-Financial Badan Usaha Milik Negara On The Indonesia Stock Exchange For The 2014-2019 Period) - Putri, Fauziah Israyani; Rokhmawati, Andewi; Haryetti, Haryetti; Rahmayanti, Elvi (Program Pascasarjana, Universitas Riau, 2021)
This study aims to examine the effect of good corporate governance, intellectual capital, and leverage on firm value with profitability as mediation variable. The population of this research was non-financial BUMN firms listed on Indonesia Stock Exchange (IDX) in 2014-2019. The sample was determined with the purposive sampling method. That obtained 18 firms as the sample. The type of data in this research was secondary data obtained from IDX. The analytical method used was Multiple Regression and Mediation Analysis, Using SPSS Software to Process data. The results of this study concluded: GCG does not significantly influence the firm value. On the other hand, Intellectual Capital, Leverage, and Profitability significantly influence the firm value. GCG does not significantly influence Profitability. Intellectual Capital and Leverage significantly influence Profitability. Profitability cannot mediate the effect of GCG and Intellectual Capital on firm value. Meanwhile, Profitability can mediate the effect of Leverage on firm value.